2011
DOI: 10.1080/17441691003796387
|View full text |Cite
|
Sign up to set email alerts
|

Structural barriers to ART adherence in Southern Africa: Challenges and potential ways forward

Abstract: Structural barriers to antiretroviral treatment (ART) adherence are economic, institutional, political and cultural factors, that collectively influence the extent to which persons living with HIV follow their medication regimens. We identify three sets of structural barriers to ART adherence that are salient in Southern Africa: poverty-related, institutional, and political and cultural. Examples of poverty-related barriers are competing demands in the context of resource-constrained settings, the lack of tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
163
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(176 citation statements)
references
References 39 publications
11
163
1
1
Order By: Relevance
“…Similar to the current study, others research has shown no significant improvement in adherence among participants who participated in group education and counseling in poor-resource settings (Safren et al, 2013;Berger et al, 2008;Sampaio-sa et al, 2008), suggesting that the study populations may have benefited from diverse types of intervention approaches, for example, an individual component, support for group members or environmental support (Thompson et al, 2012;Kagee et al, 2011;Chung et al, 2010;Kalichman et al, 2011;Haberer et al, 2013). However, several previous studies conducted in Haiti showed an improvement in HIV care and ART adherence associated with group members support (Naslund et al, 2014;Kimmel et al, 2013;Severe et al, 2010).…”
Section: Research Questionssupporting
confidence: 64%
See 1 more Smart Citation
“…Similar to the current study, others research has shown no significant improvement in adherence among participants who participated in group education and counseling in poor-resource settings (Safren et al, 2013;Berger et al, 2008;Sampaio-sa et al, 2008), suggesting that the study populations may have benefited from diverse types of intervention approaches, for example, an individual component, support for group members or environmental support (Thompson et al, 2012;Kagee et al, 2011;Chung et al, 2010;Kalichman et al, 2011;Haberer et al, 2013). However, several previous studies conducted in Haiti showed an improvement in HIV care and ART adherence associated with group members support (Naslund et al, 2014;Kimmel et al, 2013;Severe et al, 2010).…”
Section: Research Questionssupporting
confidence: 64%
“…The current study found that social support was related to adherence in this sample. Previous studies reported mixed outcomes with social support and ART adherence (Kovarth et al, 2015;Langebeek et al, 2014;Kagee et al, 2010;Beng et al, 2011;Rivero-Mendez et al, 2010;Harris et al, 2011;Tabatabai et al, 2014;Kalichman et al, 2011;Haberer et al, 2013;Kagee et al, 2011). Previous studies among Caribbean women that examined social support generally found a relationship between social support and adherence to regimen (Beng et al, 2011;Rivero-Mendez et al, 2010;Harris et al, 2011).…”
Section: Research Questionsmentioning
confidence: 99%
“…It is suggested that creating common understandings and goals for collaboration is essential, and advancing the HIV response in sub-Saharan Africa will be likely to be restricted if the full engagement of THPs is not part of the developments [19]. Successful treatment of HIV/AIDS largely depends on both systems understanding contextual and interrelated factors, as this plays a role in ART adherence for individuals using both systems alternatively or concurrently [30]. …”
Section: Discussionmentioning
confidence: 99%
“…Even when people living with HIV (PLHIV) can access HIV treatment, they continue to use THPs to complement ART, and often find support from THPs and use traditional healing for reasons not directly related to the HIV [37,41,42]. Moreover, patients sought traditional care when they could not access ART [30,43]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition to monitoring patterns of retention in care and viral suppression, GIS can be used to identify geographical barriers that may affect ART adherence, inclu ding infrastructure barriers such as inadequate transport. [52] Poor access to healthcare facilities as a result of transport challenges highlights areas for community based interventions such as adherence clubs, alternative ART distribution points and deployment of mobile clinics.…”
Section: In Practicementioning
confidence: 99%